PENGARUH MOTIVASI ORANG TUATERHADAP KEBIASAAN MENGGOSOK GIGI PADA ANAK PRASEKOLAH DI TK PERTIWI PETERONGAN KABUPATEN JOMBANG - Qoniatuz Zahroh; Endang Yuswatiningsih; Dwi Prasetyaningati (Jurnal Keperawatan, 2014)
Toothache and sore mouth often occur on pre-schoolage children, this is caused consume of sweet foods. Theirregular habit of brushing teeth can lead to tooth decay and can interfere with daily activities. This condition isdue to a lack of motivation (support) or parents guidance in doing or habituate brushing teeth to children. Thepurpose of this study was to determine the effect of parental motivation to tooth brushing habits in pre-school agechildren in kindergarten Pertiwi Village of Mancar District of PeteronganJombang.Analytic study design withcross sectional approach. The population in this study was parents who had pre-school age children with asample as many as 34 respondents, sampling was using proportional random sampling technique.Independetvariabel is parental motivation and dependent variabel is tooth brushing habits in pre-school.Datacollection was using questionnaires, data analysis was using Spearman's rank with an error rate 0,05. From theresults obtained parents’ motivation to habituate strong teeth as much as 29.4% (10), normal as much as 41,2%(14), weak was 29,4% (10). The habit of brushing teeth on in good pre-school children as much as 58.8% (20),bad as much as 41.2% (14).and then the results test of Spearman's rank showed that the P-value of 0.000 (0.000<0.05), obtained correlation coefficient of 0.779, p< 0,05 then H1 is accepted.The conclusion of this researchhad effect of parental motivation to tooth brushing habits in pre-school children in kindergarten Pertiwi villagemancar, district PeteronganJombang .Keywords : Parents motivation, tooth brushing habits.